Aloe ferox and Callistemon rigidus - Cock, I. E. (Pharmacognosy Communications)
Aloe ferox: Aloe is a genus of approximately 400 succulent plants, many of which are native to Africa. Several Aloe species have well known medicinal properties which include accelerated wound healing, as well as antimicrobial, anti-inflammatory, immunomodulatory and antioxidant bioactivities (as previously reviewed).[1,2] The species pictured (Aloe ferox, also known as Cape Aloe) is native to South Africa. Aloe ferox is reputed to be one of the most promising species of Aloe, with wide ranging therapeutic properties. This photograph was taken in Kirstenbosch Botanic Gardens, Cape Town, South Africa by Dr Ian Cock in December 2010.